National Ambulatory Medical Care Survey, 1981 ([Verlag nicht ermittelbar], 1985)
The National Ambulatory Medical Care Surveys (NAMCS) supply data on ambulatory medical care provided in physicians' offices. The 1981 survey contains information from approximately 43,000 patient visits to 1,807 physicians. Data are available on the patient's reason for the visit, the physician's diagnosis, and the kinds of diagnostic and therapeutic services rendered. Information is included on the physician's specialization and geographical location. Demographic information on patients, such as age, sex, race, and ethnicity, was also collected.